Aetonormativity and Adult Voices in the Narrative of Child Characters' Maturation in Sherlyn's Favorite Fork Comic - Putri, Indri Lestari; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Children's emotional attachment to inanimate objects often manifests as a need for security and a connection to the past. This study aims to analyze the maturation process of the protagonist, Sherlyn, in the KKPK comic Garpu Kesayangan Sherlyn by Raisha Siregar through Maria Nikolajeva’s aesthetic perspective of children’s literature. Utilizing a qualitative descriptive method, this research dissects how the symbolism of a fork functions as a "transitional object" that influences the protagonist's psychological stability. The findings reveal that Sherlyn undergoes a significant process of becoming, transitioning from destructive emotional dependence toward cognitive independence. Through the home-away-return narrative pattern, it is discovered that the loss of her cherished object serves as a catalyst for Sherlyn to develop moral agency and self-knowledge. The study concludes that Sherlyn’s transformation represents a deconstruction of the paradigm of childhood dependency, where maturity is achieved through the courage to relinquish material attachments for the sake of inner integrity. These findings reinforce the role of children’s literature as an emotional laboratory in preparing the younger generation to face loss and life changes with resilience.